2015
DOI: 10.1099/ijs.0.070078-0
|View full text |Cite
|
Sign up to set email alerts
|

Halotia gen. nov., a phylogenetically and physiologically coherent cyanobacterial genus isolated from marine coastal environments

Abstract: Nostoc is a common and well-studied genus of cyanobacteria and, according to molecular phylogeny, is a polyphyletic group. Therefore, revisions of this genus are urged in an attempt to clarify its taxonomy. Novel strains isolated from underexplored environments and assigned morphologically to the genus Nostoc are not genetically related to the 'true Nostoc' group. In this study, four strains isolated from biofilms collected in Antarctica and five strains originated from Brazilian mangroves were evaluated. Desp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(54 citation statements)
references
References 62 publications
1
52
0
1
Order By: Relevance
“…Phylogenetic studies have shown a big diversity of cyanobacteria isolated from Brazilian environments, such as mangroves (Silva et al 2014;Genuario et al 2015), salinealkaline lakes , and subaerophytic environments (Aguiar et al 2008), and new taxa were isolated and identified by ultrastructural, ecological, and molecular analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Phylogenetic studies have shown a big diversity of cyanobacteria isolated from Brazilian environments, such as mangroves (Silva et al 2014;Genuario et al 2015), salinealkaline lakes , and subaerophytic environments (Aguiar et al 2008), and new taxa were isolated and identified by ultrastructural, ecological, and molecular analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Carrying on the extensive study of cyanobacterial diversity of the Atlantic Rainforest, in which our research group has described many new taxa (sant'anna et al 2013;HentscHke & komárek 2014;genuário et al 2015;HentscHke et al 2016), we describe another new terrestrial Nostoc-like genus using a combination of 16S rRNA phylogeny, 16S-23S ITS primary sequence and secondary structures, and morphological characters visible in the light microscope.…”
Section: Introductionmentioning
confidence: 99%
“…prokaryotes (Coenye and Vandamme 2003). Further, the polyphasic approach, based on morphological, physiological and ecological and molecular characters, has been proposed to better improve cyanobacterial taxonomic assignments and revisions, therefore resulting in the description of numerous cyanobacterial genera and species (Fiore et al 2007, Bohunická et al 2015, Genuário et al 2015, Sciuto and Moro 2016, Sciuto et al 2017.…”
Section: Morphological Characterizationmentioning
confidence: 99%
“…In spite of its well-established morphological features, Nostoc has been proven to be genetically heterogeneous, and several genotypic groups were shown to fall outside of the 'Nostoc sensu stricto' clade based on 16S rRNA gene phylogeny (Hrouzek et al 2005, Rajaniemi et al 2005a, Papaefthimiou et al 2008, Lukešová et al 2009, Silva et al 2014. Therefore, the genus Nostoc has been proposed to be amended in consideration of phylogenetic data, and some Nostoc-related morphotypes have been established as new genera including Mojavia, Desmonostoc, Halotia, Komarekiella, Aliinostoc, Compactonostoc, and Minunostoc (Řeháková et al 2007, Hrouzek et al 2013, Genuário et al 2015, Bagchi et al 2017, Hentschke et al 2017, Cai et al 2019a, 2019b.…”
Section: Morphological Characterizationmentioning
confidence: 99%